The Impact of Indonesian Crude Oil Demand Prices on the Indonesian Biodiesel Industry - Siregar, Indah Adelina; Novindra, Novindra; Nofitasari, Rahmi (Universitas Galuh, 2024)
Biodiesel is one of Indonesia's potential export commodities as there is a production surplus that occurs every year from 2006 to 2020. The study used the 2SLS method with a validation and simultaneous equation model. Data processing using SAS/ETS version 9.4. The purpose of this study is to analyze the impact of Indonesia's crude oil demand price on Indonesia's biodiesel industry. The findings indicate that the demand for Indonesian biodiesel is positively impacted by a rise in the global real price of crude oil by 0.11%. This increase is due to both the biodiesel industry's and the local market's need for Indonesian palm oil. The local price of Indonesian biodiesel would rise by 0.49% due to the increase in demand for the fuel. The amount of biodiesel produced in Indonesia will increase by 0.87%, this increase in production is due to increasing domestic demand for Indonesian palm oil, and the volume of biodiesel exported to destination countries will increase by 0.01%. Exports of palm oil may be more impacted by the policy of raising the actual world price of crude oil. This implies that the program may potentially result in a rise in raw material exports. On the other hand, the biodiesel industry and other industries also see a spike in palm oil as a result of the strategy of raising the real world price of crude oil.